Adaptation Strategy for Home-Based Batik Enterprise Space in Arab Village Sugihwaras Pekalongan - Mohammad Sahid Indraswara; Atiek Suprapti; Agung Budi Sardjono; Suci Senjana; Septana Bagus Pribadi (Department of Architecture, Faculty of Science and Technology, UIN Maliki Malang, 2023)
Changes in the pattern of batik trade in Sugihwaras Arab Village encourage the community to adapt by utilising the space in their homes to become Home Based Enterprises (HBEs) of batik space. HBEs batik space is a characteristic of Sugihwaras Arab Village as a batik trading area. The people of Arab Village have adapted by implementing the